2014
DOI: 10.1073/pnas.1413112111
|View full text |Cite
|
Sign up to set email alerts
|

Quantum critical fluctuations in layered YFe 2 Al 10

Abstract: The absence of thermal fluctuations at T = 0 makes it possible to observe the inherently quantum mechanical nature of systems where the competition among correlations leads to different types of collective ground states. Our high precision measurements of the magnetic susceptibility, specific heat, and electrical resistivity in the layered compound YFe 2 Al 10 demonstrate robust field-temperature scaling, evidence that this system is naturally poised without tuning on the verge of ferromagnetic order that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…1D) [21][22][23]. Consistent with the T /B 0.6 scaling observed in the magnetization and specific heat [24], the scattering is strongly suppressed by magnetic fields B (Fig. 1A).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…1D) [21][22][23]. Consistent with the T /B 0.6 scaling observed in the magnetization and specific heat [24], the scattering is strongly suppressed by magnetic fields B (Fig. 1A).…”
supporting
confidence: 81%
“…shown that a single variable T /B 0.6 controls the QC fluctuations for a wide range of fields and temperatures in YFe 2 Al 10 [24]. This variable is also observed in neutron scattering measurements.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Initial experiments identified correlated FM behavior (Strydom and Peratheepan, 2010). Further detailed studies on single crystals found anomalies in the magnetic susceptibility and the specific heat which obey a peculiar NFL fieldtemperature scaling (Park et al, 2011;Wu et al, 2014). In addition, FM correlations have been found in NMR experiments .…”
Section: B Open Problemsmentioning
confidence: 99%